Fibrosis Assessment in Nonalcoholic Fatty Liver Disease (NAFLD) in 2016. - Kaswala, Dharmesh; Lai, Michelle; Afdhal, Nezam; Kaswala, Dharmesh H; Afdhal, Nezam H (Digestive Diseases & Sciences, 2016)
Nonalcoholic fatty liver disease (NAFLD) is a spectrum of liver pathologies characterized by hepatic steatosis with a history of little to no alcohol consumption or secondary causes of hepatic steatosis. The prevalence of NAFLD is 20-25 % of the general population in the Western countries and is associated with metabolic risk factors such as obesity, diabetes mellitus, and dyslipidemia. The spectrum of disease ranges from simple steatosis to nonalcoholic steatohepatitis, fibrosis, and cirrhosis. Advanced fibrosis is the most significant predictor of mortality in NAFLD. It is crucial to assess for the presence and degree of hepatic fibrosis in order to make therapeutic decisions and predict clinical outcomes. Liver biopsy, the current gold standard to assess the liver fibrosis, has a number of drawbacks such as invasiveness, sampling error, cost, and inter-/intra-observer variability. There are currently available a number of noninvasive tests as an alternative to liver biopsy for fibrosis staging. These noninvasive fibrosis tests are increasingly used to rule out advanced fibrosis and help guide disease management. While these noninvasive tests perform relatively well for ruling out advanced fibrosis, they also have limitations. Understanding the strengths and limitations of liver biopsy and the noninvasive tests is necessary for deciding when to use the appropriate tests in the evaluation of patients with NAFLD.